Optimal hot metal desulphurisation slag considering iron loss and sulphur removal capacity part II: evaluation. (2nd January 2021) - Schrama, Frank N. H.; Beunder, Elisabeth M.; Panda, Sourav K.; Visser, Hessel-Jan; Moosavi-Khoonsari, Elmira; Hunt, Adam; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: The optimal hot metal desulphurisation (HMD) slag is defined as a slag with a sufficient sulphur removal capacity and a low apparent viscosity ( ηslag ) which leads to low iron losses. In part I of this study, the fundamentals behind the optimal slag were discussed. In this part these fundamentals are explored by a Monte Carlo simulation, based on FactSage calculations, plant data analysis and melting point and viscosity measurements of the optimal slag. Furthermore, the applicability of knowing the optimal slag composition for an industrial HMD is discussed.